Literature Study of Biophilic Design Strategies for Improving Students’ Health and Well-Being in Schools - Putu Adelia Shindy Bella,; Pramitasari, Diananta (Nature: National Academic Journal of Architecture, 2025)
School is an educational facility that arranges teaching and learning activities according to the levels. In carrying out the learning process, students spend almost their whole time in the classroom to fulfill their learning targets. This can end up in students’ physical and mental disruptions. Therefore, there should be a design principle that can accommodate students’ health and well-being. One of the design principles that reconnects humans with nature or their environment to create a harmonious system that can provide benefits to humans in the form of health and well-being is biophilic design. This study aims to identify biophilic design strategies, evaluate their effects on student health and well-being, and examine the challenges of their implementation in case studies. The method used in this article is an integrative literature review method to see the strategies and effects of biophilic design, then a comparative study is conducted on the implementation of the theory to documented case studies using secondary data sources in three schools under the Green School International. The results of the literature review on the 14th biophilic design patterns show that there are three categories for connecting humans with nature, which were evaluated in case studies. Based on the results of the analysis, it was found that the implementation of the Nature in the Space category was seen in the integration of human sensory with natural elements, the Natural Analogues category was seen in the organic shape and materials of the building, and the Nature of the Space category was seen in the space designed to arouse students' curiosity and exploration in schools through prospect and mystery patterns.